Dugaan Pelanggaran Integrasi Vertikal dalam Bisnis Digital oleh Penyedia Jasa Transportasi Online di Indonesia (Studi Putusan KPPU Nomor 13/KPPU-I/2019) - Ananda Nurul Hidayah (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2022)
Article 14 of The Law Number 5 of 1999 highlights vertical integration as a prohibited form of agreement. One of the alleged cases of vertical integration practices is in The Case Number 13/KPPU-I/2019 involving PT GRAB Teknologi Indonesia (GRAB) and PT Teknologi Pengangkutan Indonesia (TPI), GRAB is suspected of giving privileges and priorities to TPI. This case is predicted to affect the regulation of the digital economy in the future, including investment in the digital economy sector. This study concludes: First, the Investigator stated that the agreement between GRAB and TPI led to vertical integration and discrimination due to actions taken in the form of giving special treatment that harmed other GRAB Partners who were competitors of TPI. Second, the legal consequences of violating the provisions of Article 14 of The Law Number 5 of 1999 for Business Actors are subject to sanctions in the form of Administrative Measures, Basic Criminal Sanctions, and Additional Criminal Sanctions. Meanwhile, according to Article 118 of The Law Number 11 of 2020, the sanction given to business actors who are proven to have carried out vertical integration is the imposition of Administrative Measures. Third, two of the legal reasons in Case Number 13/KPPU-I/2019 are not in accordance with the applicable legal provisions is Article 14 and Article 19 (D). But apart from that, the legal reasons in Article 15 (2) has complied with the provisions of the Anti-Monopoly Law. The business action taken by GRAB and TPI is a form of business strategy that has legal, socio-economic, technical considerations and other acceptable reasons. In addition, the agreement does not interfere with business competition because it still shows fair business competition.